Soft-tissue specimen shrinkage during the preparation for scanning electron microscopy - Wilton-Cox, H.; Cleaton-Jones, P. (My University, 1977)
The amount of shrinkage and the scanning electron microscope appearance of specimens of rat tongue, soft palate and small intestine, dehydrated by air drying , the critical point technique, the camphene technique and freeze drying were compared
KIM
Keywords: Microscopy, Electron, Scanning